Restructuring of small-scale constructed wetland systems and treatability of individual household wastewater through natural process - S. Mokatip; K. Chunkao; W. Wararam; S. Bualert; O. Phewnil; T. Pattamapitoon; N. Semvimol; P. Maskulrath; P. Rollap; S. Thaipakdee (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Domestic wastewater pollution in Thailand presents challenges due to limited space and a high concentration of point source effluents. This phenomenon often leads to domestic wastewater exceeding the capacity of local treatment systems. This study aims to expand the knowledge gained from The King’s Royally Initiated Laem Phak Bia Environmental Research and Development Project by evaluating the treatability of municipal wastewater. It utilizes a constructed wetland system in conjunction with a transfer and point source system. After the implementation of this primary system, the reduction in highly contaminated domestic wastewater could enhance the treatment loading of other secondary treatment systems or even facilitate its release into natural pathways.METHODS: In the sampling collection process, the dynamics of the collection points were categorized into three different zones: 1) the point sources of domestic wastewater within a municipality, where 15 sample points were selected to represent the municipality; 2) the collection pond within the municipality and the transfer pipeline, comprising three collection points of the system; 3) the constructed wetland treatment system, where five water samples were collected in relation to the length of the existing 100-meter plot. The water samples were collected using four 1-liter polyethylene bottles. The analysis parameters were the biological oxygen demand, total nitrogen, nitrate, total phosphorous and phosphate, and other parameters related to domestic wastewater treatment efficacy.FINDING: This study reveals that the domestic wastewater in Phetchaburi Province initially has a high organic content, leading to a biochemical oxygen demand: nitrogen: phosphorous ratio of 100:2.5:0.2 favoring anaerobic degradation. This ratio shifts in the constructed wetland system, located 18.5 kilometers away, to 100:10.5:2.3, promoting anaerobic treatment. The system shows high efficacy, with 81.4, 50.0, and 58.3 percent removal rates for biochemical oxygen demand, nitrogen, and phosphorus, respectively. This efficacy corresponds to a notable reduction in average biochemical oxygen demand from 740.0 to 9.7 milligrams per liter. Moreover, changes are observed in total nitrogen content, shifting from 20.8 to 2.8 milligrams per liter, in the system’s effluent. While lastly, the total phosphorous decreased from 2.75 to 0.60 milligrams per literCONCLUSION: This treatment method can be effectively applied to small-scale constructed wetland systems within households. The recommended hydraulic retention time is between 29 and 60 hours under anaerobic conditions and 3 days under aerobic conditions. The changes in the composition of municipal wastewater, which is highly organic, support the use of both degradation processes. The knowledge and application of the constructed wetland system could be suggested for the primary treatment system of domestic wastewater within municipalities, given that this system would provide support to the central wastewater treatment system for enhanced efficacy.